The Representation of Racial Microaggression in the Film Get Out (2017) (EUFONI: Journal of Language, Literary, and Cultural Studies, 2025)
This study examines the representation of racial microaggression in the film Get Out (2017), directed by Jordan Peele, by applying Derald Wing Sue’s theory of racial microaggressions. The study aims to analyze how racial microaggression is constructed through the experiences of the main character, Chris Washington, whose position as a Black man situates him within a predominantly white social environment. Employing a qualitative descriptive method, this research analyzes selected scenes and dialogues that portray subtle forms of racial discrimination, stereotyping, and everyday racism encountered by the protagonist. The findings reveal that racial microaggression operates as a central mechanism through which racial power relations are normalized and concealed within seemingly polite, liberal, and well-intentioned interactions. Furthermore, the film illustrates how repeated exposure to racial microaggressions generates psychological tension, marginalization, and a persistent sense of surveillance for the racialized subject. Overall, this study concludes that Get Out (2017) functions as a critical cultural text that exposes racial microaggression as a pervasive and systemic form of contemporary racism embedded in everyday social interactions and popular cinema.